2018
DOI: 10.1080/00207454.2018.1483920
|View full text |Cite
|
Sign up to set email alerts
|

Propofol post-conditioning after temporary clipping reverses oxidative stress in aneurysm surgery

Abstract: Together, our data suggest that propofol post-conditioning (Cp 1.2 µg/mL) may protect the brain from oxidative stress injury up to 7 days post-surgery after temporary parent artery clipping. Furthermore, the neuroprotection induced by propofol post-conditioning may contribute to improvement in cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In another study, 19 In our study, when we look at the evaluation of dynamic TDH within the groups and the correlation values with other markers, it was shown that propofol caused less reduction in native thiol, total thiol and disulfide values compared with desflurane in elective vertebral surgery and had a more positive contribution to oxidative stress. The findings of our study, as reported in the literature, 17,19,20 support that propofol has antioxidant properties. We can say that propofol is a better agent than desflurane in elective vertebral surgery due to its neuroprotective effects and antioxidant properties.…”
Section: Discussionmentioning
confidence: 54%
“…In another study, 19 In our study, when we look at the evaluation of dynamic TDH within the groups and the correlation values with other markers, it was shown that propofol caused less reduction in native thiol, total thiol and disulfide values compared with desflurane in elective vertebral surgery and had a more positive contribution to oxidative stress. The findings of our study, as reported in the literature, 17,19,20 support that propofol has antioxidant properties. We can say that propofol is a better agent than desflurane in elective vertebral surgery due to its neuroprotective effects and antioxidant properties.…”
Section: Discussionmentioning
confidence: 54%
“…A prospective, randomized trial by Guo et al [ 65 ] evaluated in 60 patients undergoing aneurysm clipping the role of propofol postconditioning on oxidative stress and postoperative cognitive function. The patients were randomized into a propofol postconditioning group or a sevoflurane group.…”
Section: Intravenous Anestheticsmentioning
confidence: 99%
“…Postoperatively, micronuclei as well as nucleoplasmic bridges were seen more frequently in the sevoflurane group. Finally, the propofol postconditioning group had markedly higher scores on cognitive function tests compared with the sevoflurane group after the surgery [ 65 ].…”
Section: Intravenous Anestheticsmentioning
confidence: 99%
“…In addition, cognitive function was better in the propofol treated group when measured by Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) scores up to 7 days after surgery. The authors proposed that propofol post-conditioning may protect against oxidative stress injury by enhancing antioxidation and decreasing free radical injury [ 20 ].…”
Section: Anesthetics/adjuvants In Ebi After Sahmentioning
confidence: 99%